Outcome of ovarian preservation during surgical treatment for endometrial cancer: A Taiwanese Gynecologic Oncology Group study - Hei-Yu Lau; Min-Yu Chen; Yu-Min Ke; Jen-Ruei Chen; I-Hui Chen; Wen-Shiung Liou; Hung-Chun Fu; Cheng-Chang Chang; Keng-Fu Hsu; Kung-Liahng Wang (Elsevier, 2015)
Objective: The goal of this study was to investigate the impact of ovarian preservation on the survival of women with early-stage endometrial cancer, particularly young women. Materials and methods: A study cohort of 64 patients with histologically confirmed early-stage endometrial cancer was retrospectively collected from 10 member hospitals of the Taiwanese Gynecologic Oncology Group between 1998 and 2009. Survivorship and overall survival were compared between these two groups using a log-rank test. Results: All patients who underwent surgery were adult women with a mean age of 40.4 ± 9.2 years (range 24-63 years). Ovary-preserving surgery was performed in 38 (59.4%) patients who desired to preserve their ovaries, incidentally in 19 (29.7%) patients with a preoperative diagnosis other than endometrial carcinoma, and in seven patients (10.9%) with unknown reasons. The 5-year recurrence-free survival rate was 98.3% with a median follow up of 44.6 months (range 1.0-126.9 months). Eight patients required adjuvant treatment (12.5%); one patient had documented local recurrence (1.6%); and no metachronous ovarian malignancy occurred during follow up. Conclusion: Preservation of bilateral ovaries does not increase cancer-related mortality. A more conservative approach to surgical staging may be considered in premenopausal women with early-stage endometrial cancer without risk factors.